INSILICO DESIGN OF SMALL INTERFERENCE RNA (SIRNA) FOR PREVENTION OF VIRAL (BEGOMOVIRUS) DISEASES IN COMMERCIALLY VALUABLE PLANTS (TOMATO AND PULSES) - Madhu Pearl R Gopal Pandi & Sundara Baalaji Narayanan (International Journal of Research Science and Management, 2017)
Yellow vein mosaic or yellow leaf curl disease in tomato, okra and other pulses is transmitted by Bemisia tabaci (White fly), leading to loss of production and quality. Gene silencing is one of the powerful approaches to overcome viral based plant diseases. However it is of great challenge to design potential small interfering RNA (siRNA) molecules against genes responsible for the diseases. From the primary sequence information, using insilico approach, 15 siRNAs were designed for genes involved in pathogenicity like suppressor, movement and nuclear shuttle namely V2, C2 and C4 of monopartite genome and BC1 and BV1 of bipartite genome from the Geminiviridae family. Short listing based on ranking score, GC content, base pairs, secondary structure identified 2 siRNAs for V2, 1 siRNAs for C2 and 2 siRNAs for C4, 5 siRNAs for BV1 and 5 siRNAs for BC1 genes.